Research Brief #16: Perceptions and Practices Relating to Nutrition Among Decision-Makers at Suaahara sites of Nepal. - Webb, Patrick, 1959-; Ghosh, Shibani A., 1973-; Sapkota, Diplav.; Davis, Dale.; Kennedy, Eileen T., 1947-; Gurung, Sabi; Baral, Kedar.; Rana, Pooja Pandey. (Tufts University. Tisch Library., 2016)
This brief presents preliminary findings from work in Nepal that explores issues including the processes, impacts, constraints, and innovations in multi-sectoral programming that explicitly links agriculture with health and nutrition. The focus is on Suaahara work sites. Keywords: Nutrition Innovation Lab, Research Brief, PoSHAN (Policy and Science for Health, Agriculture and Nutrition), Suaahara.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy